An Analysis of Essential Health Research in Chile [Reflexiones Sobre la Investigación Esencial en Chile] - Torres-Canales, a (Sociedad Medica de Santiago, 2017)
Essential research studies of health problems affecting the majority of the population, aiming at actions that are feasible to be taken, efficiently and effectively implementing there and seeking solutions to unsolved problems. This is a complex process, which requires long lasting participation and coordinated interaction between different relevant sectors, namely the academic world, health policymakers and health-related industries. An analysis of essential health research in Chile is presented, considering factors such as shared efforts between the academic and health care sectors and the role of the Ministry of Health in research promotion. The following suggestions are made: 1) The Ministry of Health, along with universities, should stimulate, guide and monitor research activities that enrich and update the work on priority health issues; 2) To strengthen the capacity building of clinical or public health specialists by training them in applied research within medical centers, mainly teaching centers; 3) To assess the performance of National Fund for Health Research and Development (FONIS) and, if necessary, increase its resources to stimulate applied research in health; 4) To establish priorities for essential research, more specific than those proposed in 2010; 5) To reactivate the National Council for Health Research (CONIS) as an autonomous entity that coordinates applied research within the Ministry of Health. © 2017, Sociedad Medica de Santiago. All rights reserved.
Keywords: Chile; Health priorities; Health services research; Research